Desarrollo del proceso de atención de enfermería en paciente adulto mayor con obstrucción de arteria coronaria izquierda - Méndez Mariño, Brenda Marlene (2019)
The present clinical case is about a 68-year-old male patient entering the emergency area due to intense, stinging, oppressive and retrosternal chest pain radiating to the left shoulder (angina pectoris), dyspnea, extreme fatigue make physical effort, diaphoresis for more than twenty minutes. Already for two consecutive days. Reason for which they decide to attend this house of health Specialty Hospital Nº 1 Armed Forces. Received a medical evaluation, presented a curve of altered troponins in his stay in emergencies, as well as electrocardiographic changes indicative of acute myocardial infarction, so it was decided to perform emergency coronary angiography for assessment, in which obstruction of the left coronary is found in ninety and nine percent. The nurse takes an anamnesis to obtain information about her personal pathological background, family history, allergy and surgery, based on the relevant information of the interrogation it was detected that she has high blood pressure and neurological problems she does not mention allergies, her mother suffers from high blood pressure and father is diabetic. Intervening with nursing care, obtaining favorable results that help the patient to rejoin society and continue in their daily lives.